(untitled) (JS (JURNAL SEKOLAH), 2017)
Abstract: Use of Scientific Word And Popular Word In Scientific Writing On Student.This paper discusses the use of the word scientific and popular word in the writing of scientific papers. Writing this article is motivated by the work of the authors observed among the students. Among students are very frequent confusion or kedilematisan in the use of Indonesian, especially those on the issue of the use of the word scientific and popular word. As intellectuals, students are expected to understand and differentiate what and how to say the word scientific and popular. The purpose of this study to determine the level of student understanding in the use of the word UMSU scientific and popular word in writing scientific papers and is also expected to provide input to further improve students’ ability to use the word UMSU in scientific and popular word. Keyword: Scientific Word, Popular Word, Scientific Task